Opportunities and limits of global governance by clubs - Ulrich Schneckener (Stiftung Wissenschaft und Politik (SWP), 2009)
The aftermath of the global financial crisis has seen an impressive sequence of summits - G20 in London in April, G8 in L'Aquila in July and another G20 in Pittsburgh in September. The fundamental question is: which multilateral forums are best suited for dealing with global problems? Club formats, in particular, have proliferated: from the G7/G8, the Heiligendamm Process and the Major Economies Forum to the G20 - which has in practice already met as the G20plus. The "club governance" label is widely applied to these developments. But what does it mean? What opportunities does club governance offer, and where do its limits lie? How does this approach compare with other forms of multilateral politics? What answers can it offer to the crisis of the established multilateral system? And what role can Germany, the EU and its member states play?
Keywords: 320